Features of determining the parameters of crystal lattice of ice-like associates of water molecules during hydrate formation - N.A. Shostak (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
This article describes the features of determining the enthalpy characteristics of the hydrate formation process. Aspects of forming hydrate structures from hydrate-forming agent molecules and water are described. It is shown that the processes of the hydrate formation and dissociation have different natures, which are determined by the interaction of the hydrate former with water in one phase state or another: hydrate former – solid phase of water – ice, hydrate former – liquid phase of water, hydrate former in a critical (pseudocritical) state – liquid phase of water. The dependence of the water crystallization temperature on the pressure and nature of the hydrate former is analyzed. The energy processes occurring during the formation of clusters and unit cells of the crystal lattices of hydrate structures due to the release and absorption of the thermal energy are described. Dependences are proposed for calculating the heat of formation of the crystal lattice from ice-like associates of water molecules. It is shown that the process of restructuring the ice lattice into a hydrate lattice can be both exothermic and endothermic.